Cost-effectiveness of a reactive oral cholera immunization campaign using Shanchol™ in Malawi - Patrick G. Ilboudo; Martin A. Mengel; Bradford D. Gessner; Bagrey Ngwira; Philippe Cavailler; Jean-Bernard Le Gargasson (Cost Effectiveness and Resource Allocation, 2021)
Abstract Background Oral cholera vaccines (OCV) have been recommended as additional measures for the prevention of cholera. However, little is known about the cost-effectiveness of OCV use in sub-Saharan Africa, particularly in reactive outbreak contexts. This study aimed to investigate the cost-effectiveness of the use of OCV Shanchol in response to a cholera outbreak in the Lake Chilwa area, Malawi. Methods The Excel-based Vaccine Introduction Cost-Effectiveness model was used to assess the cost-effectiveness ratios with and without indirect protection. Model input parameters were obtained from cost evaluations and epidemiological studies conducted in Malawi and published literature. One-way sensitivity and threshold analyses of cost-effectiveness ratios were performed. Results Compared with the reference scenario i.e. treatment of cholera cases, the immunization campaign would have prevented 636 and 1 020 cases of cholera without and with indirect protection, respectively. The cost-effectiveness ratios were US$19 212 per death, US$500 per case, and US$738 per DALY averted without indirect protection. They were US$10 165 per death, US$264 per case, and US$391 per DALY averted with indirect protection. The net cost per DALY averted was sensitive to four input parameters, including case fatality rate, duration of immunity (vaccine’s protective duration), discount rate and cholera incidence. Conclusion Relative to the Malawi gross domestic product per capita, the reactive OCV campaign represented a cost-effective intervention, particularly when considering indirect vaccine effects. Results will need to be assessed in other settings, e.g., during campaigns implemented directly by the Ministry of Health rather than by international partners.